About the Cultural Affiliation of the Neolithic Monuments at the Kama River Mouth - Anatoly V. Somov (Археология евразийских степей)
The paper deals with the issues of the cultural affiliation of the Neolithic assemblages at the Kama River mouth. The stroked and combed pottery assemblages identified here were initially attributed by A.Kh. Khalikov to the Volga-Kama culture. But, later, most researchers began to attribute these collections to various Neolithic cultures with different origins. Thus, the stroked ware finds analogies in the materials of the southern part of the forest-steppe Volga region, while the combed one is associated with the Neolithic groups of the Middle and Upper Kama regions. Moreover, not only their coexistence (third - last quarter of the VI BC) is recorded, but also the interaction and mixing of two traditions: Middle Volga and Kama. At the same time, the spread of the combed stamp in the forest-steppe Volga region continues to be dominated by the established technological methods of vessel construction. A similar situation is observed among the Kama population, where, with the appearance of the stroked system (Middle Volga) of ornamentation, local methods of pottery manufacture prevail. The stroked ceramics and ware with impression in the Kama River mouth area should be considered within the Volga-Kama Neolithic culture. At the same time, the isolation of combed materials from the Kama culture and their inclusion in the same culture with stroked pottery is not excluded.